1997
DOI: 10.1073/pnas.94.20.10554
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent binding to carbohydrates immobilized on an insoluble resin

Abstract: Numerous studies have established that polyvalency is a critical feature of cell surface carbohydrate recognition. Nevertheless, carbohydrate-protein interactions are typically evaluated by using assays that focus on the behavior of monovalent carbohydrate ligands in solution. It has generally been assumed that the relative affinities of monovalent carbohydrate ligands in solution correlate with their polyvalent avidities. In this paper we show that carbohydrate ligands synthesized directly on TentaGel beads i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 36 publications
1
55
2
Order By: Relevance
“…Initial experiments addressed whether the mixed SAMs were an appropriate model system to investigate specific interactions between surface-bound carbohydrates and proteins. Previous studies on TentaGel beads had shown that BP lectin recognizes ligands 1a and 2a in the presence of other structurally similar ligands, suggesting a high degree of specificity in the polyvalent interactions (6,7). Mixed SAMs presenting 1c (Fig.…”
Section: Mixed Sams As Model Systems For Assessing Protein Binding Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Initial experiments addressed whether the mixed SAMs were an appropriate model system to investigate specific interactions between surface-bound carbohydrates and proteins. Previous studies on TentaGel beads had shown that BP lectin recognizes ligands 1a and 2a in the presence of other structurally similar ligands, suggesting a high degree of specificity in the polyvalent interactions (6,7). Mixed SAMs presenting 1c (Fig.…”
Section: Mixed Sams As Model Systems For Assessing Protein Binding Tomentioning
confidence: 99%
“…Carbohydrate-protein binding events usually involve several simultaneous contacts between carbohydrates that are clustered on cell surfaces and protein receptors that contain multiple carbohydrate-binding sites. Numerous studies on model systems have demonstrated that polyvalent displays of carbohydrates can lead to remarkably high binding avidities (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because avidity and specificity are not necessarily correlated (6,7), however, polyvalency does not completely resolve the paradox of how marginally selective carbohydrate-binding interactions can produce highly specific responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have previously observed greater specificity on the part of lectins for polyvalent ligands as compared with their monovalent counterparts (15)(16)(17)(18)(19)(20)(21)(22). The specificity for multivalent ligands has been attributed to a requirement for unique spacing patterns (15)(16)(17)(18), secondary protein-protein and protein-carbohydrate interactions (19,20), and amplification in the polyvalent state of small differences in the affinities between monovalent forms (21). One prediction of a model in which small differences in affinity of monovalent ligands are amplified in the polyvalent state is that the affinities obtained for Mu11 binding to immobilized S4GGnM-BSA and S3GGnM-BSA would differ but that the B max obtained at saturation would be the same.…”
Section: Specificity Of the Cys-rich Domain For Monovalent Ligands-wementioning
confidence: 99%
“…Furthermore, the reactive centers are located at the terminus of the glycol spacers. These properties provide the opportunities for synthesizing combinatorial libraries using organic solvents followed by bioassays in aqueous media [147,148]. These resins have various size distributions ranging from TentaGel M NH 2 (diameter  10 m) to TentaGel MB NH 2 (diameter ~ 300 m) ( Table 9).…”
Section: Physical and Chemical Properties Of Pegylated Resins As Modementioning
confidence: 99%